Exploring facebook affordances in natural disaster: case study of the 2018 dead sea flash floods in Jordan - Banikalef, Alaeddin; Al Bataineh, Khaleel; Atoum, Mohammed (International Journal of Engineering and Technology, 2018)
This study observes the use of Facebook in the complex social phenomenon, natural disasters. By adopting an affordance perspective, this study emphasizes on how local Jordanian communities harness the power of Facebook during the 2018 Dead Sea flash flood. Through using an interpretive approach, three affordances of Facebook were identified, namely, disaster warning, volunteer mobilization, and the coordination of response and recovery. Then, the researchers examined how these affordances helped the Jordanian communities to respond to disaster situations and achieve social outcomes during the floods. Based on the data analysis, it has been noticed that Facebook changed the way individuals; organizations, activists, and governments respond and act to the challenges posed by a disaster. This study contributes to the emerging literature on the use of Facebook in natural disasters in the Jordanian context. There is a hope that this research could inspire more researchers about the use of emerging digital technologies in examining a variety of natural disasters.Â